Through the Kaleidoscope: Viewing the Contributions of the Behavioral and Social Sciences to Health -- The Barbara and Jerome Grossman Symposium - Institute of Medicine; National Research Council (The National Academies Press, 2002)
The importance of behavioral, social, economic, and environmental influences on health is increasingly recognized. Further, the relationships among genetic factors, social influences, and the physical environment are now of growing interest to the research, policy, public health, and clinical communities. As research in these areas yields new knowledge about these interactions, we are faced with the challenge of applying and translating that knowledge into practical applications or policy directions.To advance this challenge, the Institute of Medicine (IOM) brought together experts and collaborators at a symposium in May 2001. The symposium featured five reports released in the last 12 months by the IOM and the Division of Behavioral and Social Sciences and Education (DBASSE). The reports were the starting point for assessing the status of behavioral and social science research relating to health, identifying where the greatest opportunities appear to lie in translating this research into clinical medicine, public health, and social policy; and recognizing the barriers that continue to impede significant progress in conducting and utilizing this field of research. This report is a proceedings of the symposium from these experts in the field. Topics covered include research design, training, infrastructure investments, grant making, etiology, interventions, and priority investments necessary to support rapid advances in the behavioral and social sciences.
Keywords: Health and Medicine

Cancer and the Environment: Gene-Environment Interaction - Institute of Medicine (The National Academies Press, 2002)
The Roundtable on Environmental Health Sciences, Research, and Medicine wanted to address the link between environmental factors and the development of cancer in light of recent advances in genomics. They asked what research tools are needed, how new scientific information can be applied in a timely manner to reduce the burden of cancer, and how this can be flexible enough to treat the individual.
Keywords: Environment and Environmental Studies; Health and Medicine

Speaking of Health: Assessing Health Communication Strategies for Diverse Populations - Institute of Medicine (The National Academies Press, 2002)
We are what we eat. That old expression seems particularly poignant every time we have our blood drawn for a routine physical to check our cholesterol levels. And, it's not just what we eat that affects our health. Whole ranges of behaviors ultimately make a difference in how we feel and how we maintain our health. Lifestyle choices have enormous impact on our health and well being. But, how do we communicate the language of good health so that it is uniformly received-and accepted-by people from different cultures and backgrounds?
Keywords: Health and Medicine

Setting the Course: A Strategic Vision for Immunization: Part 2: Summary of the Austin Workshop - Institute of Medicine (The National Academies Press, 2002)
Immunization is essential to disease prevention efforts in public health, but the U.S. health care system faces financial challenges that are affecting the delivery of immunization services. An earlier report from the Institute of Medicine (IOM), Calling the Shots: Immunization Finance Policies and Practices, pointed to the instability of the fundamental infrastructure that supports immunization programs throughout the United States, including growing financial burdens and operational complexities in immunization services, shortcomings in public- and private-sector investments in vaccine purchases and immunization programs, and fluctuations in insurance plans in the public and private health care sectors that create uncertainties regarding coverage of vaccine purchase and service delivery arrangements. In October 2001, a group of about 50 health officials, public health experts, health care providers, health plan representatives and purchasers, state legislative officials, and community leaders met at the Texas Medical Association in Austin to explore the implications of the IOM findings and recommendations for Texas. The 1-day workshop was the second in a series of four meetings organized by IOM with support from the Centers for Disease Control and Prevention to foster informed discussions about challenges for immunization finance and future strategies for strengthening immunization activities and the public health infrastructure that supports those activities.This report of the Austin workshop summarizes the findings of the previous IOM report and reviews continuing challenges in immunization finance for the nation and for individual states, with a particular focus on Texas. The report also highlights strategies proposed by individual workshop participants that can be used to address those challenges. Several presenters and discussants emphasized that adequate funding is necessary for immunization programs but that financial resources alone are not sufficient to guarantee success. Similarly, they indicated that no single agency or group in the public or the private sector should expect, or should be expected, to solve immunization problems. Speakers from both public and private health agencies observed that collaboration, consultation, and partnership efforts across levels of government and between the public and private sectors are essential.
Keywords: Health and Medicine

Community Programs to Promote Youth Development - National Research Council; Institute of Medicine (The National Academies Press, 2002)
After-school programs, scout groups, community service activities, religious youth groups, and other community-based activities have long been thought to play a key role in the lives of adolescents. But what do we know about the role of such programs for today's adolescents? How can we ensure that programs are designed to successfully meet young people's developmental needs and help them become healthy, happy, and productive adults?
Keywords: Behavioral and Social Sciences; Health and Medicine

The Airliner Cabin Environment and the Health of Passengers and Crew - National Research Council (The National Academies Press, 2002)
Although poor air quality is probably not the hazard that is foremost in peoples’ minds as they board planes, it has been a concern for years. Passengers have complained about dry eyes, sore throat, dizziness, headaches, and other symptoms. Flight attendants have repeatedly raised questions about the safety of the air that they breathe. The Airliner Cabin Environment and the Health of Passengers and Crew examines in detail the aircraft environmental control systems, the sources of chemical and biological contaminants in aircraft cabins, and the toxicity and health effects associated with these contaminants. The book provides some recommendations for potential approaches for improving cabin air quality and a surveillance and research program.
Keywords: Environment and Environmental Studies

K9 Units in Public Transportation: A Guide for Decision Makers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2002)
TRB's Transit Cooperative Research Program (TCRP) Report 86: Public Transportation Security, Volume 2: K9 Units in Public Transportation: A Guide for Decision Makers offers information on current K9 deployment practices, K9 program establishment issues, and explosives detection.
Keywords: Transportation and Infrastructure

Environmental Effects of Transgenic Plants: The Scope and Adequacy of Regulation - National Research Council (The National Academies Press, 2002)
Transgenic crops offer the promise of increased agricultural productivity and better quality foods. But they also raise the specter of harmful environmental effects. In this new book, a panel of experts examines: • Similarities and differences between crops developed by conventional and transgenic methods • Potential for commercialized transgenic crops to change both agricultural and nonagricultural landscapes • How well the U.S. government is regulating transgenic crops to avoid any negative effects. Environmental Effects of Transgenic Plants provides a wealth of information about transgenic processes, previous experience with the introduction of novel crops, principles of risk assessment and management, the science behind current regulatory schemes, issues in monitoring transgenic products already on the market, and more. The book discusses public involvement—and public confidence—in biotechnology regulation. And it looks to the future, exploring the potential of genetic engineering and the prospects for environmental effects.
Keywords: Agriculture; Biology and Life Sciences

The National Plant Genome Initiative: Objectives for 2003-2008 - National Research Council (The National Academies Press, 2002)
The National Plant Genome Initiative was launched in 1998 as a long-term project to explore DNA structure and function in plants so that useful properties of plants can be understood, improved, and ultimately harnessed to address national needs, including agriculture, nutrition, energy and waste reduction. Experts in the community were asked to consider how to build on current accomplishments in order to address major questions in plant biology and to make recommendations for objectives for the next five-year phase of the Initiative.
Keywords: Biology and Life Sciences; Agriculture

Health and the Environment in the Southeastern United States: Rebuilding Unity: Workshop Summary - Institute of Medicine (The National Academies Press, 2002)
The purpose of this regional workshop in the Southeast was to broaden the environmental health perspective from its typical focus on environmental toxicology to a view that included the impact of the natural, built, and social environments on human health. Early in the planning, Roundtable members realized that the process of engaging speakers and developing an agenda for the workshop would be nearly as instructive as the workshop itself. In their efforts to encourage a wide scope of participation, Roundtable members sought input from individuals from a broad range of diverse fields-urban planners, transportation engineers, landscape architects, developers, clergy, local elected officials, heads of industry, and others. This workshop summary captures the discussions that occurred during the two-day meeting. During this workshop, four main themes were explored: (1) environmental and individual health are intrinsically intertwined; (2) traditional methods of ensuring environmental health protection, such as regulations, should be balanced by more cooperative approaches to problem solving; (3) environmental health efforts should be holistic and interdisciplinary; and (4) technological advances, along with coordinated action across educational, business, social, and political spheres, offer great hope for protecting environmental health. This workshop report is an informational document that provides a summary of the regional meeting.
Keywords: Environment and Environmental Studies; Health and Medicine

The Role of Purchasers and Payers in the Clinical Research Enterprise: Workshop Summary - Institute of Medicine (The National Academies Press, 2002)
In a workshop organized by the Clinical Research roundtable, representatives from purchaser organizations (employers), payer organizations (health plans and insurance companies), and other stakeholder organizations (voluntary health associations, clinical researchers, research organizations, and the technology community) came together to explore:
Keywords: Health and Medicine

Setting the Course: A Strategic Vision for Immunization Finance: Part 1: Summary of the Chicago Workshop - Institute of Medicine (The National Academies Press, 2002)
The federal and state partnership in supporting immunization programs that benefit the general population evolved over the last half of the 20th century from a simple cost-sharing arrangement for vaccine purchase for disadvantaged children to a more complicated mix of programs, health care coverage benefits, and public-private partnerships. The mix of financial arrangements that support immunization efforts was the subject of a study by the Institute of Medicine, resulting in the publication of the report Calling the Shots. In June 2001, a group of 50 health officials, public health experts, health care providers, health plan representatives, and community leaders met at the University of Illinois in Chicago to explore the implications of the IOM findings and recommendations for the states of Illinois and Michigan. The one-day workshop was the first in a series of four meetings organized by IOM with support from the Centers for Disease Control and Prevention to foster informed discussions about future financing strategies for the public health infrastructure that supports immunization efforts.This report of the Chicago workshop summarizes the findings of the IOM study and reviews the challenges that remain in establishing a reliable financial base for the U.S. immunization system. The report high-lights strategies presented by workshop speakers and discussants for achieving immunization goals, including increases in state and federal public health budgets, the addition of quality improvement measures in health plans, performance-based contracting, public policy actions, and the creation of public-private partnerships.
Keywords: Health and Medicine

Self-Perpetuating Structural States in Biology, Disease, and Genetics - Lindquist, Susan; Henikoff, Steve (The National Academies Press, 2002)
Keywords: Biology and Life Sciences; Health and Medicine

Estimating the Public Health Benefits of Proposed Air Pollution Regulations - National Research Council (The National Academies Press, 2002)
EPA estimates that thousands of premature deaths and cases of illnesses may be avoided by reducing air pollution. At the request of Congress, this report reviews the scientific basis of EPA's methods used in estimating the public health benefits from its air pollution regulations.
Keywords: Health and Medicine; Environment and Environmental Studies

Access to Research Data in the 21st Century: An Ongoing Dialogue Among Interested Parties: Report of a Workshop - National Research Council (The National Academies Press, 2002)
Keywords: Policy for Science and Technology; Health and Medicine

Biosolids Applied to Land: Advancing Standards and Practices - National Research Council (The National Academies Press, 2002)
The 1993 regulation (Part 503 Rule) governing the land application of biosolids was established to protect public health and the environment from reasonably anticipated adverse effects. Included in the regulation are chemical pollutant limits, operational standards designed to reduce pathogens and the attraction of disease vectors, and management practices. This report from the Board on Environmental Studies and Toxicology evaluates the technical methods and approaches used by EPA to establish those standards and practices, focusing specifically on human health protection. The report examines improvements in risk-assessment practices and advances in the scientific database since promulgation of the regulation, and makes recommendations for addressing public health concerns, uncertainties, and data gaps about the technical basis of the biosolids standards.
Keywords: Environment and Environmental Studies; Agriculture

Publicly Funded Agricultural Research and the Changing Structure of U.S. Agriculture - National Research Council (The National Academies Press, 2002)
The U.S. Department of Agriculture (USDA) requested that the Board on Agriculture and Natural Resources of the National Research Council (NRC) convene a panel of experts to examine whether publicly funded agricultural research has influenced the structure of U.S. agriculture and, if so, how. The Committee to Review the Role of Publicly Funded Agricultural Research on the Structure of U.S. Agriculture was asked to assess the role of public-sector agricultural research on changes in the size and numbers of farms, with particular emphasis on the evolution of very-large-scale operations.
Keywords: Agriculture

Dietary Risk Assessment in the WIC Program - Institute of Medicine (The National Academies Press, 2002)
Dietary Risk Assessment in the WIC Program reviews methods used to determine dietary risk based on failure to meet Dietary Guidelines for applicants to the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Applicants to the WIC program must be at nutritional risk to be eligible for program benefits. Although “dietary risk” is only one of five nutrition risk categories, it is the category most commonly reported among WIC applicants. This book documents that nearly all low-income women in the childbearing years and children 2 years and over are at risk because their diets fail to meet the recommended numbers of servings of the food guide pyramid. The committee recommends that all women and children (ages 2-4 years) who meet the eligibility requirements based on income, categorical and residency status also be presumed to meet the requirement of nutrition risk. By presuming that all who meet the categorical and income eligibility requirements are at dietary risk, WIC retains its potential for preventing and correcting nutrition-related problems while avoiding serious misclassification errors that could lead to denial of services for eligible individuals.
Keywords: Food and Nutrition

The Genomic Revolution: Unveiling the Unity of Life - Yudell, Michael; DeSalle, Robert (The National Academies Press, 2002)
Keywords: Explore Science; Health and Medicine; Biology and Life Sciences

Proposed Framework for Evaluating the Safety of Dietary Supplements -- For Comment - Institute of Medicine (The National Academies Press, 2002)
Keywords: Food and Nutrition